(3JPcQI GdcMGdjfs - (3GdcMGd, Ydj Hf YjSi Hf Ydj, J (B430 (3g`s
(3ChdgG (B:s
(3HSe Gddg gPg QSGdI CdaJgG LhGHG YeG SCdg efj HYV ENhGfj aj JYQja GeQGV GdYjf hYdGLgG ; hUd cJGHc JSCd Yf LhGeY cJGH LGdjfhS aj GeQGV GdYjf s
(3BNQgG (B:s
(3MhQO HOdg fhaQ hRd jOd RHdg RHd GdNGWa MQa GdjGA ; jGSejf ThT , jHQhM dbGM hHPQI , jHJhY HOdg VYag SHjcfL , jGbhJ HOdg VYag PgH hbO Je GdcJGHs
(3JHUQI GdeDda (B:s
(3LGA GSeg ceG hQO aj ebOeI GdeNWhW (B: ( (3YjSi Hf Ydj (B) (3aj CNHGQ GdYdeGA ddbaWj (B1/189 (3h eYLe GdeDdajf (B2/596 (3, hGdeKHJ eG hQO aj Yjhf GdCfHGA dGHf CHj CUjHYI (B1/333 (3, hGdhGaj HGdhajGJ ddUaOj (B21/247 (3h GdCYdGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4/318s
(3cTa GdXfhf (B2/1474s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs